Intraoperative crush cytology in the diagnosis of neurosurgical cases - Madhavan, Madhavan; Singh, Gurjeet Kaur d/o Chatar; P, Jain George (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Intraoperative cytologic smears in neurosurgery are easy to perform and inexpensive and permit reasonably high diagnostic accuracy. Even very tiny specimens, especially of soft consistency are suitable for this technique, which is extremely important in operation of tumours localized in functionally important brain areas. The cytologic diagnosis could be made based on the presence of characteristic cytomorphological features. Very high accuracy can be archived in certain tumours like nerve sheath tumour, germinoma, meningioma, metastasis, grade II astrocytoma, pituitary adenoma and oligidendroglioma. However, the accuracy is low in high grade glioma, medulloblastoma and ependymoma. In the absence of their diagnostic cytomorphological features, the correlation with clinicoradiological features might help in arriving at the correct diagnostic and increase their diagnostic accuracy. Further studies involving more number of cases is needed to find out the value of crush cytology in diagnosing the rare tumours and inflammatory lesions. In cytology examination, presence of pure normal glial tissue has high negative predictive value. This helps in guidance during targeting the lesions including steriotactic biopsy and also during the resection of infiltrative lesions for definition of tumour margins.